2022
DOI: 10.1101/2022.04.21.22273941
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A statistical genomics framework to trace bacterial genomic predictors of clinical outcomes in Staphylococcus aureus bacteraemia

Abstract: Outcomes for patients with severe bacterial infections are determined by the interplay between host, pathogen, and treatments. Most notably, patient age and antibiotic resistance contributes significantly to poor outcomes. While human genomics studies have provided insights into the host genetic factors impacting outcomes of Staphylococcus aureus infections, comparatively little is known about S. aureus genotypes and disease severity. Building on the idea that bacterial pathoadaptation is a key driver of clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 73 publications
3
7
0
Order By: Relevance
“…Major MDS axes correlated with the most prevalent STs, for example ST239 was mainly defined by MDS1 (negative correlation) and MDS2 (positive correlation) (Figure 4-Supplementary Figure 3A). We then tested the association between the first 10 MDS axes (90% of the genetic variance explained) and the PI uptake phenotype in Pyseer (Earle et al, 2016;Giulieri, Guérillot, Holmes, et al, 2022;Lees et al, 2018). In agreement with the initial observations based on the phylogeny and cytotoxicity heatmap (Figure 4A), we observed significant cytotoxicity-lineage associations represented by MDS3 and MDS4 (Figure 4D, Figure 4-Supplementary Figure 2).…”
Section: Gwas Analysis Using Intoxsa Outputs To Identify S Aureus Gen...supporting
confidence: 81%
See 4 more Smart Citations
“…Major MDS axes correlated with the most prevalent STs, for example ST239 was mainly defined by MDS1 (negative correlation) and MDS2 (positive correlation) (Figure 4-Supplementary Figure 3A). We then tested the association between the first 10 MDS axes (90% of the genetic variance explained) and the PI uptake phenotype in Pyseer (Earle et al, 2016;Giulieri, Guérillot, Holmes, et al, 2022;Lees et al, 2018). In agreement with the initial observations based on the phylogeny and cytotoxicity heatmap (Figure 4A), we observed significant cytotoxicity-lineage associations represented by MDS3 and MDS4 (Figure 4D, Figure 4-Supplementary Figure 2).…”
Section: Gwas Analysis Using Intoxsa Outputs To Identify S Aureus Gen...supporting
confidence: 81%
“…While intracellular cytotoxicity was strongly associated with some S. aureus lineages, this analysis showed that lineage alone does not completely explain the phenotype, as indicated by the significant overlap between the three cytotoxicity clusters across MDS3 and MDS4 (Figure 4D). This pattern is consistent with other adaptive phenotypes (Earle et al, 2016;Giulieri, Guérillot, Holmes, et al, 2022;Su et al, 2021) and suggests that locus effects from specific micro-evolutionary events modulate cytotoxicity, supporting the use of GWAS and convergent evolution approaches to identify these mutations.…”
Section: Gwas Analysis Using Intoxsa Outputs To Identify S Aureus Gen...supporting
confidence: 80%
See 3 more Smart Citations